Transformative learning as societal learning. Issue 177 (14th February 2023) - Formenti, Laura; Hoggan‐Kloubert, Tetyana
Abstract: The article synthesizes literature relating to the recent development of the theory of transformative learning (TL) and societal changes using three exemplary fields of study: (1) Civic education and democratic transformations, (2) TL for sustainability and ecology, and (3) TL in the context of migration (and especially for refugees). This article contends that in the literature, TL is considered a promising answer to an urgent search for conceptual and practical tools to address the wicked problems of our time. We see, however, also the potential pitfall of TL if used as a buzzword or understood as a comprehensive reeducation program designed from above that ignores human agency and the emotional, relational, and political challenges of transformation.